A novel method for evaluating sun visible light protection factor and pigmentation protection factor of sunscreens - Schalka S; de Paula Corrêa M; Sawada LY; Canale CC; de Andrade TN (Clinical, Cosmetic and Investigational Dermatology, 2019)
Sérgio Schalka,1 Marcelo de Paula Corrêa,2 Leticia Yumi Sawada,1 Camila C Canale,3 Thayna N de Andrade41Department of Dermatology, Medcin Clinical Research Center, Osasco, Brazil; 2Institute of Natural Resources, Federal University of Itajubá, Itajubá, Brazil; 3Department of Pharmacy, Medcin Clinical Research Center, Osasco, Brazil; 4Department of Photoprotection, Medcin Clinical Research Center, Osasco, BrazilCorrespondence: Sérgio SchalkaDepartment of Dermatology, Medicine Clinical Research Center, Rua Atílio Delanina 178, Osasco 06023-000, SP, BrazilTel +55 113 654 2054Email sergio.schalka@medcin.com.brIntroduction: The role of visible light (VL) in the process of skin pigmentation by solar radiation has been demonstrated. Sunscreens with the presence of pigments, particularly iron oxide (IO), have a greater protective effect against VL and are, therefore, highly recommended for prevention and treatment of hyperpigmentation disorders. This study aimed to evaluate 33 sunscreen formulations, and through spectrophotometric measurements, proposes new methods to evaluate the VL protection factor and the pigmentation protection factor.Methods: 33 sunscreen formulations marketed in Brazil were evaluated, including 17 products containing pigments and 16 products with no pigments. Spectrophotometric measurements were taken to determine solar VL protection factor and the pigmentation protection factor, based on the absorption curve of the product, the pigmentation action spectrum and sun spectrum.Results: Sunscreen with pigments presented a higher solar VL protection factor and pigmentation protection factor compared to products without pigment. The statistical analysis showed a strong correlation between the solar VL protection factor and the integral of the absorption curve in the VL range and the transmittance reduction (%) in the same range. The correlation between the VL protection factor and the pigmentation protection factor was also demonstrated.Conclusion: The VL protection factor and the pigmentation protection factor showed to be adequate metrics to estimate the effectiveness of sunscreens in the prevention of the pigmentary effect of solar VL and the pigmentary effect of the complete spectrum of immediate pigmentation.Keywords: visible light, sunscreening agents, sun protection factor, skin pigmentation